THE INFLUENCE OF STAD TYPE COOPERATIVE LEARNING MODEL ON HEAT MATERIAL AND ITS TRANSFER ON CRITICAL THINKING ABILITY AND SCIENCE LEARNING OUTCOMES - Yulia Rahmawati; Sutarto Sutarto; Nur Ahmad (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2024)
The development of education is marked by advances in science and technology which cause every individual to have the ability "The 4Cs". Low critical thinking caused who are passive and teachers who do not package learning in an interesting way resulting in learning heat material. So, it overcome through the selection of a learning model, namely the STAD. The researchers aimed to examine the significant effect of the STAD on critical thinking skills and learning outcomes. This quasi-experimental study used a non-equivalent control group design. The research location is at SMPN 10 Jember in semester of 2022/2023. The conclusions of the entire test are, (1) the STAD-type cooperative learning model on heat material and its locking have a significant effect on students thinking abilities, and (2) the STAD-type cooperative learning model on heat material and its locking have a significant effect on science learning outcomes for junior high school students.